CHALLENGING THE INTERPRETATION OF THE VERSE ON HIJAB BY M. QURAISH SHIHAB: A CRITICAL ANALYSIS REVIEW - Rohman, Abdul; Muttaqien, Ghazi Abdullah; ALMonawer, Faisal Hamad; Rumanian, Tigran; Deik, Mohammad (Universitas Muhammadiyah Surakarta, 2024)
There is a variety of interpretations regarding the verse on the hijab in the Qur'an. Some commentaries demonstrate strong arguments, while others appear to be subjective and ambiguous. This article examines the thoughts of Quraish Shihab on the hijab verse and critically analyzes them. The research falls under the category of library research, utilizing a descriptive analysis method to explain research findings based on the study's focus with a critical analysis to produce objective results. The approach employed is content analysis. The primary sources for this research are the Tafsir Al-Mishbah and Jilbab Pakaian Wanita Muslimah. The research findings indicate: First, Quraish Shihab argues that wearing the hijab is not obligatory but merely a recommendation and is applicable only in the time of Prophet Muhammad. Scholars also do not agree on the limits of women's modesty, and the rules of the hijab are considered part of Arab cultural traditions, not applicable to other nations that do not wear the hijab. Second, Quraish Shihab's interpretation of the hijab verse lacks strong arguments in the context of Islamic studies. The wording of the command in the hijab verse is still regarded as an obligation and cannot be transformed into a recommendation due to the lack of supporting evidence. Scholars have unanimously agreed on the limits of women's modesty, from the top of the head to the tips of the toes, excluding the face and the palms of the hands. The law of the hijab remains in effect until the end of time, even though it was revealed under specific conditions and in specific regions, as Islam is considered a universal religion.